Study to compare open surgery, endovenous thermal ablation and ultrasound guided foam sclerotherapy for treatment of varicose veins - Pandey, Sandeep Raj (Journal of Society of Surgeons of Nepal, 2016)
Introduction and Objective: To compare open surgery, Endovenous thermal ablation(EVTA) and ultrasound(USG) guided foam sclerotherapy for primary superficial venous insufficiency(PVI) with respect to obliteration of superficial venous system at 3 months, clinical outcome and cost. Materials and Methods: Between January 2015 to January 2016, all patients with symptomatic PVI of lower limbs who were willing for definitive management were randomized to open surgery (n=20), EVTA (n=40) or ultrasound guided foam sclerotherapy (n=20). In foam sclerotherapy group, review USG was done at 1 week and if necessary re-injection was done. The patients in all the groups underwent review USG at 3 months. Obliteration of superficial venous system, clinical outcome and costs were registered. Results: 5 patients in foam sclerotherapy group required re-injection at 1 week. Superficial venous system was obliterated in all the patients of all the groups at 3 months. Improvement in clinical score was similar in all groups. The foam sclerotherapy group had less frequent analgesia intake, earlier return to normal activity and lower cost. Local complication rate was slightly higher in foam sclerotherapy group. Conclusion: Foam sclerotherapy is a cheaper alternative to open surgery & EVTA for PVI with respective to early measures of clinical outcome. USG guided sclerotherapy demonstrated to be a safe and effective procedure for the treatment of chronic venous insufficiency. The observed complications were minimal and most of the patients reported satisfaction with the treatment outcomes. If patient have no cost issue, endovenous thermal ablation of varicose veins is better than open surgery & foam sclera in context of minimally invasive, cosmetic, less pain, no incisions, early ambulation & same day discharge.